Association of body mass index and PXDNL gene variants with acute primary angle closure in southern Chinese population - Chen, Jiawei; Chen, Shaowan; Zheng, Yuqian; Xu, Yanxuan; Zhong, Xin; Huang, Yuqiang; Ng, Tsz Kin; Huang, Chukai (Heliyon, 2023)
This study aimed to evaluate the association of body mass index (BMI) and the weight-related gene, peroxidasin-like (PXDNL), with acute primary angle closure (APAC) and primary angle-closure glaucoma (PACG) in southern Chinese population. Total 4700 study subjects (1024 APAC, 781 PACG, and 2895 control subjects) with complete ophthalmic examinations were enrolled into this study. The association of BMI with APAC, PACG and ocular biometric parameters was evaluated. Three PXDNL missense variants were genotyped by TaqMan assay, and their association with APAC and PACG was also investigated. Multivariable logistic regression analysis showed that BMI and body weight were significantly associated with both APAC and PACG (P < 0.01). Multiple linear regression analysis demonstrated that each 1 kg/m2 increased in BMI was associated with 0.038 mm increase in axial length, 0.018 mm increase in central anterior chamber depth, 0.002 mm increase in lens position, 0.012 mm increase in corneal diameter and 0.014 mm decrease in lens thickness among the APAC subjects (P < 0.001), but not with PACG. Genetic association analysis identified that PXDNL rs11985241–rs16916207 CT haplotype conferred a higher risk to APAC (OR = 1.25, P = 0.004) than the TG haplotype, but not with PACG. The APAC subjects carrying the rs11985241 C or rs16916207 T alleles showed significantly lower weight than those carrying the corresponding protective alleles. In summary, this study revealed that lower BMI could be associated with higher risk of APAC. PXDNL could be a new associated gene for APAC.